174k views
18 votes
What should be added to 4x²-3x²+1 to make it a perfect square​

User Theveloper
by
6.4k points

2 Answers

11 votes
You could solve this by using completing the square and simplifying
User Ichthyocentaurs
by
5.7k points
10 votes


im \: guessing \: its \: 4x {}^(2) - 3x + 1 \\ (correct \: me \: if \: im \: wrong)


(a - b) {}^(2) = a {}^(2) - 2ab + {b}^(2)


4x {}^(2) = a {}^(2) \: \: \: \: \: \: \: \: \: \: \: b {}^(2) = 1 \\ a = 2x \: \: \: \: \: \: \: \: \: \: \: \: \: \: b = 1


(2x - 1) {}^(2) = 4x {}^(2) -4x + 1


we \: need \: to \: add \: a \: - x \\ \: to \: the \: original \: equation

Note that this problem can be approached in many ways. For instance, we can add to the b² term instead of changing the middle term...

User Mahdieh Shavandi
by
5.3k points